Enhancing Cultural Consciousness - Willis, Steve (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2023)
Student engagement and empowerment promote active, first-person conversations with national and international scholars and artists through virtual presentations. The process discussed below establishes a procedure for student-directed learning and empowerment. This process can be applied to any publications, internet resources, videos, YouTube conversations, and so much more to develop multinarrative and multicultural learning opportunities. Active learning is evident in student reflections that were collected throughout the Fall 2020 semester. By accepting this process of empowering students through active, authentic learning, changes to the syllabus, curricula, and pedagogy had to be made. There is excitement about the potentiality presented by future students as they engage in a similar process of the analysis of chapters, ongoing Blackboard discussions, and how they approach encounters with scholars and artists through a virtual medium.